Wind tunnel modelling of boundary layer of wind profile in sururban terrain [electronic resource] - Soo, Wei Hung, 1988-; Roslida Abd. Samat (2012)
Project Paper (Sarjana Muda Kejuruteraan (Awam))- Universiti Teknologi Malaysia, 2012